2013
DOI: 10.1161/atvbaha.112.300142
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Control of Vascular Endothelial Growth Factor Signaling Output During Vascular Development

Abstract: The regulated response of endothelial cells (ECs) to signals in their environment is not only critical for the de novo formation of primordial vascular networks during early development (i.e. vasculogenesis), but is also required for the subsequent growth and remodelling of new blood vessels from pre-existing ones (i.e. angiogenesis). Vascular endothelial growth factors (Vegfs) and their endothelial-cell specific receptors play a crucial role in nearly all aspects of blood vessel growth. How the outputs from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 104 publications
(157 reference statements)
0
53
0
Order By: Relevance
“…[17][18][19] Here, we revealed by real-time PCR assay that the expression of frizzled-4 (Frz4), a member of frizzled receptor of the Wnt signaling pathway, was also upregulated in the corneal epithelia of rats after corneal suture surgery, compared with that in control rats (Fig. 1B).…”
Section: Corneal Suture Induces Mir-184 Down-regulation and Frizzled-mentioning
confidence: 85%
“…[17][18][19] Here, we revealed by real-time PCR assay that the expression of frizzled-4 (Frz4), a member of frizzled receptor of the Wnt signaling pathway, was also upregulated in the corneal epithelia of rats after corneal suture surgery, compared with that in control rats (Fig. 1B).…”
Section: Corneal Suture Induces Mir-184 Down-regulation and Frizzled-mentioning
confidence: 85%
“…Regulation of angiogenesis by miRNAs occurs in both physiological and pathological conditions where both pro-and anti-angiogenic mRNAs can be targeted. 116 The most widely studied pro-angiogenic factor is VEGF, and miRNA-mediated control over angiogenesis, specifically by modulating VEGF transcripts, has been demonstrated. [117][118][119][120][121] While there are many pro-and anti-angiogenic miRNAs, each member of the miRNA-17-92 cluster (miR-17, -18a, -19a, -19b, -20a and -92a), has been shown to have anti-angiogenic effects on endothelial cell sprouting in vitro and inhibition of these miRNAs increased endothelial sprouting.…”
Section: Microrna Regulation Of Angiogenesismentioning
confidence: 99%
“…(Refer to Ref [14] for a thorough review). Among them, miR-126 is the most extensively studied for its role in maintaining vessel integrity and directing angiogenesis.…”
Section: Mirna and Endothelial Differentiationmentioning
confidence: 99%
“…RISC complex finally repress mRNA translation and/or induce mRNA degradation, with the latter playing a predominant role [12]. Over the past several years, there has been an increasing amount of evidence suggesting that miRNAs are implicated in regulation of EC development, phenotype and function [13,14]. It has been suggested that miRNAs play a divergent role in EC development and differentiation from stem cells: some can maintain stem cells pluripotence, while other promote their differentiation into specific lineages depending on the targets it regulates.…”
Section: Introductionmentioning
confidence: 99%